Bank liquidity provision across the firm size distribution - Gabriel Chodorow-Reich; Olivier Darmouni; Stephan Luck; Matthew Plosser (Federal Reserve Bank of New York, 2020)
Using loan-level data covering two-thirds of all corporate loans from U.S. banks, we document that SMEs (i) obtain much shorter maturity credit lines than large firms; (ii) have less active maturity management and therefore frequently have expiring credit; (iii) post more collateral on both credit lines and term loans; (iv) have higher utilization rates in normal times; and (v) pay higher spreads, even conditional on other firm characteristics. We present a theory of loan terms that rationalizes these facts as the equilibrium outcome of a trade-off between commitment and discretion. We test the model's prediction that small firms may be unable to access liquidity when large shocks arrive using data on drawdowns in the COVID recession. Consistent with the theory, the increase in bank credit in 2020:Q1 and 2020:Q2 came almost entirely from drawdowns by large firms on pre-committed lines of credit. Differences in demand for liquidity cannot fully explain the differences in drawdown rates by firm size, as we show that large firms also exhibited much higher sensitivity of drawdowns to industry-level measures of exposure to the COVID recession. Finally, we match the bank data to a list of participants in the Paycheck Protection Program (PPP) and show that SME recipients of PPP loans reduced their non-PPP bank borrowing in 2020:Q2 by between 53 and 125 percent of the amount of their PPP funds, suggesting that government-sponsored liquidity can overcome private credit constraints.
Keywords: G00; G20; G30; 330; liquidity provision; macro-finance; credit; financial constraints; loan terms; banking; credit lines; COVID-19